Rdp1, a Novel Zinc Finger Protein, Regulates the DNA Damage Response of rhp51(+) from Schizosaccharomyces pombe - Shim, Young Sam (American Society for Microbiology, 2000)
The Schizosaccharomyces pombe DNA repair gene rhp51(+) encodes a RecA-like protein with the DNA-dependent ATPase activity required for homologous recombination. The level of the rhp51(+) transcript is increased by a variety of DNA-damaging agents. Its promoter has two cis-acting DNA damage-responsive elements (DREs) responsible for DNA damage inducibility. Here we report identification of Rdp1, which regulates rhp51(+) expression through the DRE of rhp51(+). The protein contains a zinc finger and a polyalanine tract similar to ones previously implicated in DNA binding and transactivation or repression, respectively. In vitro footprinting and competitive binding assays indicate that the core consensus sequences (NGG/TTG/A) of DRE are crucial for the binding of Rdp1. Mutations of both DRE1 and DRE2 affected the damage-induced expression of rhp51(+), indicating that both DREs are required for transcriptional activation. In addition, mutations in the DREs significantly reduced survival rates after exposure to DNA-damaging agents, demonstrating that the damage response of rhp51(+) enhances the cellular repair capacity. Surprisingly, haploid cells containing a complete rdp1 deletion could not be recovered, indicating that rdp1(+) is essential for cell viability and implying the existence of other target genes. Furthermore, the DNA damage-dependent expression of rhp51(+) was significantly reduced in checkpoint mutants, raising the possibility that Rdp1 may mediate damage checkpoint-dependent transcription of rhp51(+).